Praktik Pembelian Tanah Wakaf Secara Kolektif Menurut Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf (Studi Kasus Masjid Daarussalam, Kota Wisata Bogor) - Adawiyyah, Nur Laila Maulida; Hasan, Nur; Munir, Muhammad Misbakul (Journal of Computer Science and Information System(JCoInS), 2024)
This research discusses observations of Law Number 41 concerning Waqf in the context of the practice of purchasing land for waqf done collectively. explained in a mosque, namely the Mosque Darussalam in Tourism City, Bogor. Purchase of land for waqf collective is an act of charity that can be carried out by individuals, group, or institution to acquire land or property with purpose of waqf. Waqf is a concept in Islam where a person or a group donates assets (usually land or property) to charitable or public interest purposes. The main purpose of waqf is to improve social and community welfare. This research examine relevant aspects, such as land purchasing practices, type of waqf used, pillars and terms of waqf according to Law Number 41 of 2004. This research method uses qualitative approach with data collection through interviews mosque administrators, identify related aspects with Law Number 41 concerning waqf, nadzir, power of attorney and property ownership, allocation of waqf assets. Research result shows that the practice of purchasing land for waqf is carried out collectively at the Darussalam Mosque Foundation is appropriate with the Waqf Law number 41 of 2004.